NUMERALS WITH APPROXIMATION SEMANTICS IN A FICTION TEXT IN TRANSLATION - O.N. Golubkova (Многоязычие в образовательном пространстве, 2023)
The article examines the translation of numerals in the first ten, and the methods of translation are studied by comparing the original in Russian and the English translation. This comparison helps to describe possible variants in English, which broadens the understanding of the bilingual correspondences of numerals. The aim of the article is to identify patterns of translation of the numerals of the first ten in the fiction text on the basis of a comparative analysis. In the poetics of short stories, the numerals fulfil the artistic function of recreating the authenticity of the depicted, with a focus on objectivity, characteristic of the individual style of A.P. Chekhov. One way of realizing this is through the use of numerals with the meaning of approximation, which creates the effect of the lack of awareness of the narrator, emphasizing his qualities of an outside observer. A comparison of the numerals in the original and the translations of Chekhov’s stories shows that the target language has a sufficient arsenal to convey the approximation of the original numerals. The most frequent way of transferring the approximation of numerals is the grammatical substitution of a noun, pronoun or adverb, with some cases of the original numeral being replaced by another numeral not only in cases of mismatched measures of length and distance, but also of time, age or the quantitative characteristics of individual objects. The neglecting of the inverted word order, which recreates the approximation sense in some contexts of the original text, as well as individual cases of inattention to the preservation of numerals in the phraseological units have been considered to be a translation loss.